Analysis of Interest in Learning Mathematics of Junior High School Students Using Open-Ended Approach Geogebra Assissted - Elenne Rhizkita Akbar; Anik Yuliani; Puji Nurfauziah (IKIP Siliwangi, 2023)
The aim of this study is to analyze students' interest in learning mathematics using open-ended approach with the help of software geogebra. This study used a qualitative descriptive method, with 29 students from 8th grade in SMP Negeri 36 Bandung as subjects, consisting of 14 male students and 15 female students. The data collection technique uses a questionnaire on the scale of students' interest in learning mathematics using an open-ended approach with the help of software geogebra. There are 18 statements consisting of nine positive statements and nine negative statements. The data collected from this study is processed using Microsoft Excel by calculating the average percentage of each indicator scale of student interest in learning. The results of data processing show that students have an interest in learning mathematics using open-ended approach with the help of software geogebra included in the very good category, namely obtaining an average percentage of 80.95%. The average is obtained from each index of student interest in learning. Used of the method purposed is proven to be very helpful for students in building interest in learning in mathematics.